Chitosan Mempertipis Dinding dan Memperbesar Diameter Lumen Arteri Koroner Tikus Putih yang Diberi Pakan Lemak Tinggi (CHITOSAN COULD THINEN WALL AND WIDEN LUMEN DIAMETER CORONARY ARTERY OF SPRAGUE DAWLEY RATS INDUCED BY HIGH FAT RATION) - Isdadiyanto, Sri; Moeljopawiro, Sukarti; Puniawati, Nyoman; Wuryastuty, Hastari (Jurnal Veteriner, 2013)
The objective of this study was to analyze the influence of chitosan on coronary artery wall thicknessand lumen diameter of Sprague Dawley rats induced by high fat ration. The animals for this study weretwenty adult male rats divided into four groups, i.e. group I as the control was fed with basal rationcontaining normal fat for 3 months, group II was fed ration containing high fat for three months, group IIIwas fed ration containing high fat and given chitosan 180 mg per kg body weight per day orally in 2 mLaquadest for 3 months, group IV was fed ration containing high fat for three months and after one monthgiven chitosan 180 mg per kg body weight per day orally in 2 mL aquadest for two months. Each groupconsisted of five animals. After 90 days, the rats were necropsied and the hearts were collected tohistopathological. The difference between treatments was statistical analysis by Anava, and continued byLowest Significant Difference Test to locate the difference. Normal fat ration did not influence coronaryartery wall thickness and coronary artery lumen diameter in rats. High fat ration increased coronaryartery wall thickness and chitosan could be decreased coronary artery wall thickness in rats. High fatration + chitosan that given simultaneously could be increased coronary artery lumen diameter in rats.Based on the result of this study, it was concluded that high fat ration was a major factor able to causeatherosclerosis and chitosan was able to prevent atheroma plaque formation.
Keywords: Atherosclerosis, chitosan, coronary artery wall thickness, coronary artery lumen diameter, high fat ration